How voltage-gated calcium channels gate forms of homeostatic synaptic plasticity - Frank, C. Andrew (Frontiers in Cellular Neuroscience, 2014)
Throughout life, animals face a variety of challenges such as developmental growth, the presence of toxins, or changes in temperature. Neuronal circuits and synapses respond to challenges by executing an array of neuroplasticity paradigms. Some paradigms allow neurons to up- or downregulate activity outputs, while countervailing ones ensure that outputs remain within appropriate physiological ranges. A growing body of evidence suggests that homeostatic synaptic plasticity (HSP) is critical in the latter case. Voltage-gated calcium channels gate forms of HSP. Presynaptically, the aggregate data show that when synapse activity is weakened, homeostatic signaling systems can act to correct impairments, in part by increasing calcium influx through presynaptic CaV2-type channels. Increased calcium influx is often accompanied by parallel increases in the size of active zones and the size of the readily releasable pool of presynaptic vesicles. These changes coincide with homeostatic enhancements of neurotransmitter release. Postsynaptically, there is a great deal of evidence that reduced network activity and loss of calcium influx through CaV1-type calcium channels also results in adaptive homeostatic signaling. Some adaptations drive presynaptic enhancements of vesicle pool size and turnover rate via retrograde signaling, as well as de novo insertion of postsynaptic neurotransmitter receptors. Enhanced calcium influx through CaV1 after network activation or single cell stimulation can elicit the opposite response – homeostatic depression via removal of excitatory receptors. There exist intriguing links between HSP and calcium channelopathies – such as forms of epilepsy, migraine, ataxia, and myasthenia. The episodic nature of some of these disorders suggests alternating periods of stable and unstable function. Uncovering information about how calcium channels are regulated in the context of HSP could be relevant toward understanding these and other disorders.